Forming Community-Based Eco-Travel Intentions in Small Island Destinations: How Norms and Environmental Responsibility Interact with Attitude and Behavioral Control - Sri Ismulyati; Ginta Ginting; Andriyansah Andriyansah (AIBPM Publisher, 2026)
Small island destinations are highly vulnerable ecosystems where sustainable tourism depends on community participation and environmentally responsible tourist behavior. This study integrates the Theory of Planned Behavior (TPB) and Value–Belief–Norm (VBN) Theory to examine factors influencing tourists’ community-based eco-travel intentions. Data were collected from 289 tourists visiting small island destinations in Indonesia and analyzed using PLS-Structural Equation Modeling (SEM). The results show that personal norms, social norms, and environmental responsibility significantly enhance tourists’ attitudes toward community-based eco-travel, while attitude positively influences behavioral intention. Attitude also partially mediates the relationships between these antecedent variables and behavioral intention. However, perceived behavioral control does not moderate the relationship between attitude and intention. These findings suggest that positive attitudes alone do not necessarily translate into stronger eco-travel intentions. The study contributes to sustainable tourism literature by highlighting the importance of normative influences and environmental responsibility in promoting community-based eco-tourism and supporting the long-term sustainability of small island destinations.